(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
Arganne with the accession name Acc. 202209sno3-5) is a fenugreek variety released by Oromia Agricultural Research Institute, Sinana Agricultural Research Center, Ethiopia in 2021. The trial was conducted at Sinana Agricultural Research Centre from observation nursery to preliminary yield trial and promising fenugreek genotypes were selected from yield trial based on seed yield and reaction to diseases, especially powdery mildew. These promising genotypes were evaluated against standard check Hunda’ol and Ebisa across three locations for three consecutive years (2017 to 2019). Arganne showed superior yielding ability, producing a mean seed yield of 17-26 Qt ha-1 on the research field and 15-21 Qt ha-1 on the farmers’ field. The seed yield of the new variety exceeded that of the standard check Hunda’ol and Ebisa varieties by about 12.00% and 11.23%, respectively. Int. J. Agril. Res. Innov. Tech. 12(2): 53-55, December 2022